THE MEANING OF COMMUNAL EATING ACCORDING TO JESUS AND THE THEOLOGICAL-MISSIOLOGICAL IMPLICATIONS FOR MINISTRY IN INDONESIA - Lumintang, Ramly Donald Belly (Moriah Theological Seminary, 2025)
Eating together has become a tradition and custom deeply embedded in almost all ethnicities, races, and cultures in Indonesian society. Eating together is typically done during traditional and religious celebrations, and has even become a routine and programmed activity of churches. Eating together aims to foster intimacy, friendship, and family ties, fostering mutual tolerance. Sometimes, this purpose has faded, with eating together becoming simply a shared meal and then being finished. In the Gospels, Jesus also shared a meal with tax collectors and sinners, with the purpose of proclaiming the message of forgiveness of sins and eternal salvation. Jesus shared more than just a meal; it also had theological and missiological significance. The church must return to the principles of sitting down to a meal like Jesus'.